Alcohol Outlets and Violent Crime in Washington D.C - Franklin, F. Abron (Western journal of emergency medicine, 2010)
Objective: Alcohol is more likely than any other drug to be involved in substance-related violence. In 2000 violence-related and self-directed injuries accounted for an estimated $37 billion and $33 billion in productivity losses and medical treatment, respectively. A review of emergency department data revealed violence and clinically identified trauma-related injuries have the strongest correlation among alcohol-dependent injuries. At the environmental level there is a relationship between alcohol outlet density and violent crime. A limited number of studies have examined the relationship between alcohol outlet type and the components of violent crime. The aim of this study is to examine the relationship between the aggregate components of violent crime and alcohol outlet density by type of outlet.Methods: For this study we used Washington, D.C. census tract data from the 2000 census to examine neighborhood characteristics. Alcohol outlet, violent crime, and population-level data for Washington, D.C. were drawn from various official yet publicly available sources. We developed an analytic database to examine the relationship between alcohol outlet category and four types of violent crime. After estimating spatial correlation and determining spatial dependence, we used a negative binomial regression analysis to assess the alcohol availability-violent crime association, while controlling for structural correlates of violence.Results: Independent of alternative structural correlates of violent crime, including the prevalence of weapons and illicit drugs, community-level alcohol outlet density is significantly associated with assaultive violence. Outlets were significantly related to robbery, assault, and sexual offenses. In addition, the relationship among on-premise and off-premise outlets varied across violent crime categories.Conclusion: In Washington, D.C., alcohol outlet density is significantly associated with the violent crimes. The science regarding alcohol outlet density and alcohol-related harms has clearly identified the use of limiting outlet density to reduce the associated adverse health consequences. Moreover, the disproportionate burden among poor urban and minority communities underscores the urgency to develop context-appropriate policies to regulate the functioning of current alcohol outlet establishments and to prevent the proliferation of future outlets. [West J Emerg Med. 2010; 11(3): 284-291.